JUNG’S ANIMUS OF THE FEMALE MAIN CHARACTERS IN THE WOMAN KING FILM - Kuang Yu; Essy Syam; Sorta Hutahaean (UIN Alauddin Makassar, 2024)
The Animus Archetype has four stages of development, this research uses data collection in documentation technique. The data are obtained by analyzing dialogues, expressions, and actions of the female main characters in The Woman King film. The data analyzing uses interactive method. The result of this research shows that the female main characters reflect the masculine traits in their actions parallel to Animus development stages of The Man of Power, The Man of Action, The Man of Word, The Man of Meaning. In the man of power, the female main characters act in their actions by showing strong physique, using weapons, blades, spears in the battle and killing enemies. They are brave, energetic, forceful, persistent in doing their activities, such as: climbing high, jumping in soldiers training, threatening enemies, debating in royal meeting. Then, in the stage of the man of word, the female main characters utter words of encouragement to encourage their warriors preparing to fight or reminding some slogans of soldier to the warriors. The last stage is the man of meaning, they dream to be a great man figure, like one of the female main characters wanted to be a soldier and another character was elevated by Dahomey King to be The Woman King with sacred title of Kpojito which had equal position with Dahomey King after ruining the Oyo analyzed using an interactive method.